Electrochemical and viscoelastic evolution of dodecyl sulfate-doped polypyrrole films during electrochemical cycling. (10th April 2017) - Gao, Wanli; Sel, Ozlem; Perrot, Hubert
Abstract: The correlation between electrochemical and viscoelastic properties of electrodeposited dodecylsulfate-doped polypyrrole (PPy-DS) during electrochemical cycling process was described through combining electrochemical quartz-crystal microbalance (EQCM), ac -electrogravimetric characterizations and electroacoustic measurements. As the PPy-DS electrode evolves during the course of consecutive cycling in aqueous NaCl electrolyte, the film exhibits ( i ) an obvious ion-selective transition from cations to anions in the charge compensation process; ( ii ) an inferior electrochemical performance accompanied with increased stiffness (increased storage moduli, Ǵ); and ( iii ) depleted capability of ionic exchange through film/electrolyte interface. PPy-DS conducting polymer electrodes (CPEs) are of interest in energy storage and the relationship between electrochemical and viscoelastic properties during electrochemical cycling process is essential for promoting the performance of these devices. In this perspective, ac -electrogravimetry combined with electroacoustic measurements can be suggested as an alternative method to synchronously probe the electrochemical and mechanical evolution and has the potential to offer a generalized route to study aging mechanism of CPEs.